أهمية مشعرات الكرية الحمراء في التفريق بين فقر الدم بعوز الحديد و التلاسيميا الصغرى - عثمان, منير; حيدر, أحمد; ديب, باسم (Latakia University Journal -Medical Sciences Series, 2019)
إنّ فقر الدم بعوز الحديد و التلاسيميا الصغرى السببان الأشيع لفقر الدم ناقص الحجم و الصباغ . و قد استخدمت بعض المشعرات الكريوية للتمييز السريع بينهما . حُسبت ستة مشعرات كريوية في تعداد دم 198 طفلا تراوحت أعمارهم بين (1-14) عاما، لديهم (↓MCVو↓MCH) و ذلك بعد إتمام تشخيص الحالات سريريا و مخبريا (129 حالة عوز حديد و 69 تلاسيميا صغرى) و ذلك لتبيان أهمية هذه المشعرات في التفريق بين المرضين بحساب قيمة مشعر Youden الإحصائي لها. أظهرت النتائج أن أياً من هذه المشعرات لم يظهر حساسية ونوعية 100%، لكن أفضل قيم يودن كانت لمشعر Mentzer و Srivastava (76.49% -76.39%) على الترتيب، و تبين أنه في الحالات التي يتوافق فيها المشعران السابقان في الدلالة على تشخيص واحد نحصل على (92.93% نسبة تشخيص بنجاح مع قيمة يودن 82.44% ) . بالنتيجة : يمكن الاعتماد على المشعرات الكريوية لتوجيه التشخيص بنسبة كبيرة، لكن تأكيده يحتاج إلى دراسة حالة الحديد و نسبة الخضاب A2 إلى أن نتمكن من تطوير مشعرات موثوقة. Iron deficiency anemia (IDA) and thalassemia minor (TM) are the most common forms of microcytic anemia. Some discrimination indices calculated from red blood cell indices are defined and used for rapid discrimination between TM and IDA. We calculated six red blood cell indices in 198 patients between (1-14) years old with microcytic anemia. After a complete clinical and laboratory study to diagnose each of our patients, we got (129 patients with IDA and 69 with TM) to determine the importance of these indices in differentiation between the two diseases by calculating Youden’s index to them. Results showed none of the discrimination indices had a sensitivity and specificity of 100%. Mentzer and Srivastava indices had the highest Youden’s index value (76.49%-76.39%) respectively. When the two indexes refer to the same diagnosis (Mentzer& Srivastava) we get a new index achieve (92.93% of the patients were correctly identified and Youden’s index =82.44%). Conclusion: we can use red blood cell indices to guide the diagnosis; but total body iron status and haemoglobin A2 level should be obtained for accurate differential diagnosis of IDA and TM until more efficient tools develop.